Podjetništvo med željami in stvarnostjo : Global Entrepreneurship Monitor 2005 - Rebernik, Miroslav; Tominc, Polona; Pušnik, Ksenja (2006)
Entrepreneurship between Wishes and Reality : Global Entrepreneurship Monitor 2005. The Global Entrepreneurship Monitor (GEM) tries to determine differences between countries regarding the level of entrepreneurial activity, reveals factors leading to adequate level of entrepreneurial activity and suggests measures that would lead to its improvement. Present study extends aspects of entrepreneurial analysis into more categories than previous years. New to the GEM methodology is the monitoring of established businesses. These are businesses which are older than three years and a half. Entrepreneurship is a complex phenomenon where the entrepreneurial activity cannot be simply defined with the entrepreneurs included in nascent and new ventures (TEA). Present study shows progress in some areas, which are: increased involvement of adult population in the entrepreneurial activity, increase of opportunity-driven entrepreneurship, increased involvement of females into entrepreneurship, decreased level of discontinuation rate of nascent ventures, etc. But it also highlighted many weaknesses, which are: low innovativeness of established businesses (ventures), weak educational structure of entrepreneurs, cultural norms’ aversion to entrepreneurship, deficiency of appropriate entrepreneurship education and training, etc.
Keywords: podjetništvo; Globalni podjetniški monitor; ustaljena podjetja; inovacijska naravnanost; rast; Entrepreneurship; Global Entrepreneurship Monitor; Established Businesses; Innovativeness; Growth